Development of Augmented Reality-based Learning Media to Improve Students' Understanding of Moral Affairs Lessons in Class IX MTs - Hasanah, Uswatun; Asri, widiatsih; Eges Tri, Wahyuni (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The product developed in this media is an Augmented Reality-based learning medium that is an application. Basically, Augmented Reality media is a software to create 3D image, video, text and audio devices into a program created.The study aims to determine the effectiveness and level of students' understanding of the material of faith to the last days using the Augmented Reality media. Research and development techniques, or simply